Electrical Trees in a Composite Insulating System Consisted of Epoxy Resin and Mica: The Case of Multiple Mica Sheets For Machine Insulation - Kioussis, V. A.; Danikas, M.; Christantoni, D. D.; Vardakis, G. E.; Bairaktari, Α. (Engineering, Technology & Applied Science Research, 2014)
Epoxy resin and mica sheets consist the essential insulation of rotating machine stator bars. Such an insulation, although very resistant to partial discharges, is subjected to considerable electrical stresses and consequently electrical trees may ensue. In this paper, an effort is made to simulate electrical tree propagation in multiple epoxy resin/mica sheets with the aid of Cellular Automata (CA). An attempt to compare the simulation results with experimental results is also made.